“Donki” Migration of Refugees from South Asia to Greece - Taukeer, Mohammed (Border Crossing, 2022)
This article focused on the study of irregular “Donki” migration of refugees from South Asia to Greece in Europe. The study is based on the field survey which was conducted in August 2017 in Athens, Greece. The primary data was collected by method of qualitative study design. The finding of study show that “Donki” migration is associated with unauthorised migration of refugees from South Asia to Europe due to hopes of better life in Europe compared to South Asia. The “Donki” migration is synonyms with the hurdles and bravery in the views of South Asian refugees because South Asian refugees face political, economic and geographical challenges with psychological distress in the entire journey of migration from South Asia to Europe. This study encourages academics, researchers and policy makers to understand the meaning, determinants and consequences of “Donki” migration. It is hoped to be useful for better policies for management of the challenges faced by South Asian refugees in Europe.